Empowerment of fishermen’s wives through management of agriculture products in Tanjung Saleh, Kubu Raya Regency - Kusumayanti, Fitri; Prakoso, Imam Agung; Gafallo, Muhamad Fadhil Yarda (Community Empowerment, 2025)
This activity aims to empower fishermen’s wives through the management of agricultural products in Tanjung Saleh Village, Kubu Raya Regency. The village is located in a coastal area rich in marine and agricultural resources, but these resources have not been optimally utilized to improve the welfare of the community, especially fishermen's wives. Through training and mentoring, the activity focuses on enhancing skills in processing marine products (such as fish) and agricultural products (such as coconuts) into value-added products, specifically serundeng. This activity employs a participatory action research approach, complemented by a qualitative method in data collection. The results indicate an increase in participants' knowledge and skills in processing serundeng.